The Role of The Library in Increasing Students' Learning Motivation: Peranan Pustakawan Dalam Meningkatkan Motivasi Belajar Siswa - Cahyadi, Muhammad Teguh Bambang; Nafisah, Syifaun (Universitas Airlangga, 2025)
Background: Learning motivation is an essential aspect of student success in the learning process. In this context, librarians play a crucial role in enhancing student learning motivation by implementing various strategies to optimize learning activities. Optimal learning can improve student achievement. Efforts to realize this goal make librarians very important in educating the nation's young generation. Purpose: Exploration in this study focuses on data collection on the role of librarians in their various efforts to increase student learning motivation. Method: This study uses a literature review approach, which is an approach to a study related to data collection methods by utilizing books and articles as primary data sources. Findings: From the results of this study, librarians play an essential role in increasing learning motivation. Conclusion: Librarians can make this happen by providing sources of information, helping them to search for information/references, organizing literacy activities, providing support to students, providing technology, creating attractive room designs, and working with teachers. This role will help students become more creative and active during the learning process and can help them develop optimally. Keywords: librarian role, learning motivation, student achievement, library services, literature review ——————————————————————————————————————————————————————– PERAN PERPUSTAKAAN PERGURUAN TINGGI DALAM MENINGKATKAN LITERASI DIGITAL MAHASISWA PASCASARJANA UNIVERSITAS NEGERI MALANG ABSTRAKLatar Belakang: Motivasi belajar merupakan aspek penting dalam keberhasilan siswa dalam proses pembelajaran. Dalam aspek ini, Pustakawan berperan penting dalam meningkatkan motivasi belajar siswa melalui berbagai upaya untuk mengoptimalkan kegiatan pembelajaran. Pembelajaran yang optimal dapat meningkatkan prestasi siswa. Upaya untuk mewujudkan tujuan tersebut menjadikan pustakawan sangat penting dalam mencerdaskan generasi muda bangsa. Tujuan: Eksplorasi pada penelitian ini berfokus pada penggalian data mengenai peran pustakawan dengan berbagai upayanya untuk ikut berpartisipasi dalam meningkatkan motivasi belajar para siswa. Metode: Penelitian ini menggunakan pendekatan pengkajian kepustakaan, yaitu pendekatan pada sebuah penelitian yang berkaitan dengan metode pengumpulan data dengan memanfaatkan buku dan artikel sebagai sumber data primer. Temuan: Dari hasil penelitian ini terlihat jelas bahwa pustakawan memegang peranan penting dalam meningkatkan motivasi belajar. Kesimpulan: Pustakawan dapat mewujudkannya dengan menyediakan sumber informasi, membantu pencarian informasi atau referensi, menyelenggarakan kegiatan literasi, memberikan dukungan kepada siswa, menyediakan teknologi, membuat desain ruangan yang menarik, dan bekerja sama dengan guru. Peran tersebut akan membantu siswa menjadi lebih kreatif dan aktif selama proses pembelajaran serta dapat membantu mereka berkembang secara optimal. kata kunci: motivasi belajar, peran pustakawan, prestasi siswa, layanan perpustakaan, kajian pustaka